Reaction to late blight in response to nitrogen management in Argentine potato cultivars - Cicore, Pablo L. (2012)
The objective of this study was to evaluate the reaction to late blight of two potato cultivars in response to nitrogen (N) management under field and in Vitro conditions. In Balcarce trial a reduction in phenols with the addition of excess N was found. Despite the reduction of the concentration of phenols no differences in the relative area under disease progress curve (rAUDPC) were observed between N levels. In Tafí del Valle, the rAUDPC denoted an interaction between cultivar and N level. In Frital, the N0 showed lower rAUDPC than N optimal (Opt) and N excessive (Exc) treatments. In contrast, no differences in rAUDPC between N levels on Pampeana were found. In the detached leaf test, no significant differences between N levels were observed in the threshold of severity of disease and the lesion growth rate. In conclusion, excessive N fertilization did not increase the susceptibility to late blight in this study.